CESifo World Economic Survey February 2008 - Gernot Nerb; Anna Stangl (CESifo World Economic Survey, 2008)
World Economic Climate: World Economic Climate deteriorates further - Economic Expectations: Assessments of the current economic situation and economic expectations downgraded - Inflation: Higher inflation expected in 2008 - Interest Rates: Decline expected - Currencies: US dollar and Japanese yen remain undervalued - Special Topic: Internet governance
Keywords: 330